Ecogeochemistry Kola - Field Manual - Äyräs, Matti; Reimann, Clemens (1995)
During the period 1994-1996, the Geological Survey of Norway (NGU) and Finland (GTK) and the Central Kola Expedition (CKE) are carrying out a joint project on eco-geochemical mapping and monitoring within an area extending from longi- tudes 24\u00B0 to 35 \u00B030' and southwards to the Arctic Circle in Finland and to the boundary between the Murmansk and Karelia regions in Russia. As a part of this project, a detailed study of eights catchment areas (three in Finland, one in Norway, and four in Russia) was carried out during 1994. The following sample media were taken for this catchment study; snowpack, topsoil, stream water, organic stream sediment, rainwater, moss, podzol pro- files, groundwater, rocks and Quaternary deposits. In 1995, regional sampling will be carried out at a density of 1 sampling station per 300 km\u00B0 throughout the project area. Sample media for this regional study are: humus (0-3cm) podzol profiles (5 layers) terrestrial moss and top- soil (0-5cm, for radionuclide analysis). In the Russian project area, lake water samples will also be taken. This manual contains all information and intructions given to the field samp- ling teams. The first part describes the methods used for the catchment study, the second part gives the intructions for the regional sampling in 1995 and the third part gives a short description of the equipment that we specially developed for this project. 34343